Organization Communication for Leadership Training Program to Create Sustainability - Pinariya, Bernadette H U; Pinariya, Janette Maria; Yulianti, Wulan (Yayasan Ilomata, 2024)
Communication by a leader plays an important role in the process of conveying information, ideas and other things within an organisation. A leader's ability to communicate with employees, stakeholders, and clients in the most effective way is key. How organisational communication is applied in the training programme received by leaders. In the practice, decision-making, miscommunication, and ineffectiveness of activities still have the potential to occur. For this reason, research organization communication flow for leadership training program is needed. So that the company's business can be effective and sustainable. This research using a qualitative approach will deepen and analyse. The informants used as sources in this research are project leaders, expert instructors, organisational communication experts, user/client representatives and business development. The results showed the importance of having organisational communication to make training effective. The communication chosen should be in accordance with the culture of the organisation, and the success of the training also needs to be communicated to the public so that the organisation has good institutional value. Effective communication plays an important role in the success of leadership training programmes that aim to promote sustainability in business organisations.